'The needs of the child have been met': preliminary assessments regarding domestic violence in Swedish Child Protections Services. Issue 2 (2nd April 2020) - Münger, Ann-Charlotte; Mattsson, Tina
ABSTRACT: The Swedish Child Protection Services (CPS) are responsible for providing support and protection to children experiencing domestic violence, but in a high proportion of cases where there is a suspicion that children are experiencing violence, no investigation is opened. The aim of this article is to explore on what grounds decisions were made not to open an investigation in cases initiated due to concerns that a child might have been experiencing domestic violence. The analysis is based on qualitative data consisting of 116 preliminary assessments that resulted in the cases being closed without further action. The analysis uses a theoretical model in which the CPS sorting process is understood as a way of describing a case in such a way that it fits into the organisation's problem categories, rules and procedures. The analysis shows that a set of institutional assumptions and presuppositions affect the decision to screen out cases involving this form of child abuse. The legal requirement for voluntary parental cooperation has a profound impact on the outcome of a case. Cases are also screened out when the case workers find that parental cooperation is limited. Nor are there procedures for dealing with (psychological) violence that is not aimed directly at the child, but occurs between the parents. The outcome in these cases is that the parents' interpretation is given precedence, while the needs of the child are seen as of less importance and become deprioritised.